If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -11 = 0 Reorder the terms: -11 + 9x = 0 Solving -11 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 9x = 0 + 11 Combine like terms: -11 + 11 = 0 0 + 9x = 0 + 11 9x = 0 + 11 Combine like terms: 0 + 11 = 11 9x = 11 Divide each side by '9'. x = 1.222222222 Simplifying x = 1.222222222
| 3w+16=4 | | -4-10-x=25 | | 12y-4-6y=4 | | a-(2a-4)= | | 8y+16c=24 | | 4z+16=4 | | (16x+8x-20x+3x)= | | 8y+8c=16 | | 3xy+4xy= | | 3x+12=-2x+72 | | 3x^2-5x+16= | | 8y+8c=24 | | x^4+10x^3+35x^2+50x+24=0 | | 3y+9=24 | | 5x+2=5-2x | | 4y+4c=16 | | 6m-47=7 | | U=6v | | 3y+9c=12 | | 3y+9c=24 | | 7=6m-47 | | 3y+9c=15 | | x^3-2(x^2)+2x=400 | | 3y+9c=21 | | 69-w=173 | | 3x-19=x-15 | | 8x-2(4+x)=7 | | 2+6x-4=0 | | 5(5y+2)=4(2y-5) | | log(1024)= | | 17x-(8x-9)=81 | | -5x-3+7x=0 |